Development and evaluation of a nanopore 16S rRNA gene sequencing service for same day targeted treatment of bacterial respiratory infection in the intensive care unit. Issue 2 (August 2021) - Baldan, Rossella; Cliff, Penelope R.; Burns, Sarah; Medina, Adela; Smith, Graeme C.; Batra, Rahul; Cerda, Alberto; Wilson, Rebekah; Merrill, Tammy; Lewis, Shona J.; Patel, Amita; Jeyaratnam, Dakshika; et al.
Highlights: Nanopore sequencing can provide a same day result for respiratory infection on ICU. Nanopore 16S sequencing was able to identify causative pathogen in 32/33 cases. Providing a sequenced negative result adds value to patient management. Further work is required to standardise and automate this technology for routine use. Summary: Objectives: Assess the feasibility and impact of nanopore-based 16S rRNA gene sequencing (Np16S) service on antibiotic treatment for acute severe pneumonia on the intensive care unit (ICU). Methods: Speciation and sequencing accuracy of Np16S on isolates with bioinformatics pipeline optimisation, followed by technical evaluation including quality checks and clinical-reporting criteria analysing stored respiratory samples using single-sample flow cells. Pilot service comparing Np16S results with all routine respiratory tests and impact on same-day antimicrobial prescribing. Results: Np16S correctly identified 140/167 (84%) isolates after 1h sequencing and passed quality control criteria including reproducibility and limit-of-detection. Sequencing of 108 stored respiratory samples showed concordance with routine culture in 80.5% of cases and established technical and clinical reporting criteria. A 10-week same-day pilot Np16S service analysed 45 samples from 37 patients with suspected community (n=15) or hospital acquired (n=30) pneumonia. Np16S showed concordance compared with all routine culture or molecular tests for 27 (82%) of 33 positive samples. It identified the causative pathogen in 32/33 (97%) samples and contributed to antimicrobial treatment changes for 30 patients (67%). Conclusions: This study demonstrates feasibility of providing a routine same-day nanopore sequencing service that makes a significant contribution to early antibiotic prescribing for bacterial pneumonia in the ICU.